Genetic etiology of 283 Chinese individuals with epilepsy using copy number variation sequencing and whole exome sequencing: a single-center cohort study - Junji Hu; Min Xin; Jinxiu Liu; Hongxing Li; Xuemei Li; Longchang Chen; Ping Yang; Haiyan Zhao; Pengfei Sun; Guodong Gao; Hu Feng; Zhongxia Li; et al. (BMC Medical Genomics)
Abstract Background The genetic etiology of epilepsy is highly heterogeneous and complex. Copy number variation sequencing (CNV-seq) and whole exome sequencing (WES) have emerged as effective tools for identifying genetic causes in patients with unexplained epilepsy. This study aimed to investigate the genetic etiology, evaluate the diagnostic utility of concurrent CNV-seq and WES, and provide evidence for precision medicine and genetic counseling. Methods We conducted a retrospective cohort study of 283 patients with unexplained epilepsy undergoing WES and 228 patients undergoing CNV-seq, with partial cohort overlap (n = 228). The diagnostic efficiency, its correlation with demographic information, and the clinical impacts of gene diagnostic results on clinical decision-making were assessed. Results A genetic diagnosis was obtained in 81 patients (28.6%). Among these, 67 (23.7%) had SNVs/Indels, 13 (4.6%) exhibited CNVs, and one (0.3%) displayed dual molecular findings of pathogenic SNV and CNV. The combined approach increased diagnostic yield to 30.7% (70/228) compared to standalone WES (27.9%, 79/283) or CNV-seq (6.1%, 14/228). Trio-based whole exome sequencing (trio-WES) demonstrated a higher diagnostic rate (33.3%, 7/21 vs. 27.5%, 72/262 proband-only WES). The predominant pathogenic genes identified were SCN1A (n = 14), PRRT2 (n = 5), GABRG2 (n = 4), and TSC1 (n = 4). Twenty-four novel SNVs/Indels were identified. Diagnostic yield correlated significantly with early seizure onset [< 3 year: 41.5% vs. ≥3 year: 20.9%; OR (95%CI): 2.685 (1.581–4.560), p = 2.569 × 10− 4] and the presence of other comorbidities [45.9% vs. 17.4%; OR (95%CI): 4.023 (2.338–6.922), p = 4.950 × 10− 7]. Genetic findings directly informed anti-seizure medication optimization in 42.0% (34/81) of diagnosed cases. Conclusions This dual sequencing approach enhances diagnostic yield in unexplained epilepsy, with trio-WES providing incremental yield. The strong genotype-phenotype correlations underscore the prognostic value of molecular diagnosis, while the 42% clinical utility rate highlights its translational relevance. Our findings expand the epilepsy mutational spectrum and enhance genetic understanding of epilepsy.